Quality of Banking Sustainability Reports: Symbolic or Substantive? - Saraswati, Erwin; Rachmawati, Yuliana; Anjani, Andan (European Journal of Applied Sciences, 2023)
Banking sector has an important role in sustainability report disclosure, even though the operational activity has no direct impact to the environment and society. Corporate Social Responsibility (CSR) disclosure will create positive social image to the society, moreover bank sustainable activities can affect the reputation that will be use as competitive advantage. Financial Services Authority Regulation Number 51/POJK.03/2017 requires financial institution to make sustainability report because banks are facilitators of industrial activities that damage the environment. This research aims to examine sustainability report practice, GRI standard application, assurance and quality of banking sustainability report disclosure in Indonesia. Besides the GRI standards, this research also uses GRI G4 specifically for financial sector, with consideration that can be obtained more relevant disclosures. Sample used is as much as 42 banking industries during 2017-2019 period with the total of 126 observations, using the purposive sampling method. Hypothesis testing using panel regression. The adoption of GRI standards can enhance the quality of CSR information in the banking sector, whereas the adoption of separate sustainability reporting and assurance practices can diminish its quality. This implies that sustainability disclosures made by banks tend to be more symbolic than substantive. The research findings endorse the legitimacy theory.